2022
DOI: 10.1093/fampra/cmac024
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and consequences of violence against healthcare workers in Turkey: before and during the COVID-19 pandemic

Abstract: Background Before and throughout the COVID-19 pandemic, healthcare workers (HCWs) were victims of workplace violence (WPV). There are no reliable statistics on the occurrence and consequences of WPV against HCWs in Turkey throughout the pandemic period. Objective We investigated the rates of WPV against HCWs in Turkey in the pre-pandemic and pandemic periods, variables associated with WPV, and the relationship between these v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
(17 reference statements)
0
14
0
Order By: Relevance
“…Patient violence towards medical staff has become an increasingly common occurrence in healthcare settings worldwide (Ozdamar Unal et al, 2022 ). The COVID-19 global pandemic exposed this situation which poses serious challenges to the safety, and mental and physical wellbeing of medical staff (Bellman et al, 2022 ; Catton, 2020 ; Romate & Rajkumar, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patient violence towards medical staff has become an increasingly common occurrence in healthcare settings worldwide (Ozdamar Unal et al, 2022 ). The COVID-19 global pandemic exposed this situation which poses serious challenges to the safety, and mental and physical wellbeing of medical staff (Bellman et al, 2022 ; Catton, 2020 ; Romate & Rajkumar, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Ramzi et al [ 45 ] revealed that the prevalence of violence against healthcare professionals during COVID-19 pandemic was 47% [ 45 ]. Several studies from Turkey also showed that a high rate of the health professionals were affected by violence before and during the pandemic [ 46 , 47 ]. Consistent with the literature [ 45 – 47 ], the present study also showed that almost half of the nurses (45.80%) were exposed to violence.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from Turkey also showed that a high rate of the health professionals were affected by violence before and during the pandemic [ 46 , 47 ]. Consistent with the literature [ 45 – 47 ], the present study also showed that almost half of the nurses (45.80%) were exposed to violence. It was surprising that exposure to violence did not have an effect on COVID-19 burnout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond that, increased exposure to physical violence is perhaps the most crucial factor that should not be ignored. In fragile countries with toxic organizational structures, the absence of strict laws has fuelled the rates of violence and put health workers in an unfavourable position [ 8 ]. In fact, the idea that they are more likely to be punished in case of a complaint despite being subjected to violence or that the legal sanctions against the perpetrator of the violent act are not going to not work was adopted by some HWs and led to an increase in psychological problems.…”
Section: Quiet Quitting: a Significant Risk For Global Healthcarementioning
confidence: 99%